Serum paraoxonase- 1 activity in children: The effects of obesity and insulin resistance - (:unkn) unknown (Acta Cardiologica, 2014)
Oxidative stress (OS) is important in the pathogenesis of atherosclerosis. Paraoxonase-1 (PON1) is an enzyme found in the circulation associated with high-density lipoprotein (HDL). HDL-associated enzyme PON1 has an important role in the attenuation of atherogenic low-density lipoprotein (LDL) oxidation. The aim of this study was to determine PON1 and arylesterase (AREST) enzyme levels in relation to insulin resistance (IR) or obesity among children and adolescents. The study included healthy school children and adolescents. Blood was drawn for the determination of blood glucose, lipid, PON1 and AREST enzyme levels. Overall, we observed a positive correlation between PON1 enzyme activity and high-density lipoprotein cholesterol (HDL-C) levels (r = 0.189, P = 0.014). The correlation appeared to be more significant in boys (r = 0.271, P = 0.009). For subjects with IR and obesity, PON1 enzyme activity did not correlate with HDL-C levels (r = 0.038, P = 0.790), instead PON1 levels correlated negatively with BMI (r = − 0.309 and P = 0.026). Multiple linear regression analysis was performed to find the predictors of log PON1 activity. HDL-C level was the strongest predictor of PON1 activity in the lean control group, while BMI appeared to be the strongest predictor in the subjects with obesity or IR. In conclusion, determinants of PON1 enzyme activity are variable in children and adolescents based on IR and obesity. Future studies will shed light on the underlying mechanisms and biomarkers of OS in children and may reveal possible targets for therapeutic intervention. © 2014, Acta Cardiologica. All rights reserved.
Keywords: Children; HDL-C; Insulin resistance; Oxidative stress; Paraoxonase